Metal matrix composites with ternary intermetallic inclusions fabricated by laser direct energy deposition. (1st January 2018) - Shishkovsky, Igor; Missemer, Floran; Smurov, Igor
Highlights: Rapid alloy prototyping approach for functional gradient MMC was shown. Double and triple intermetallic phases, which reinforced MMC, were fabricated during LDED. Possibility of phase-structural controlling of the layerwise FG MMC was estimated. Abstract: At the present research, we obtained the metal matrix composites (MMC) of dispersion-reinforced nickel and titanium based alloys with variable content, structure and properties using laser direct energy deposition (LDED). We have ascertained that forming double and triple reinforced MexAly (x, y = 1.0.3) intermetallic structures with preset parameters of dispersibility and spatial distribution can be performed in-situ, using the LDED during the phase transformations of cooling and crystallization of the alloy. The preset gradients of final chemical composition, structure and microhardness have been obtained precisely by regulating the composition of the powder mixture supplied to the active zone of the LDED. We suggest a combination method of the LDED which can be an effective instrument for search and development of the new MMC and alloys for the additive manufacture field, as well as for studying structure- and phase-formation in the nonequilibrium conditions of laser synthesis.